Avoiding the Trap of Parallelism: Interlocking Parallel Style in the Interpretation of Laozi 29 - Fech, Andrej (Religions, 2022)
The present paper deals with a specific argumentative feature found in the Laozi, namely, “interlocking parallel style” or IPS. It shows how knowledge of this structure can be helpful for the understanding and interpretation of the text. At the same time, the paper demonstrates that, in some cases, rigorously imposing IPS can be counterproductive. To this end, the paper analyses Laozi 29, the commentary to it penned by Wang Bi, as well as a close parallel in the fifth chapter of the Wenzi.